2023
DOI: 10.3389/fnmol.2023.1194769
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan catabolites, inflammation, and insulin resistance as determinants of chronic fatigue syndrome and affective symptoms in long COVID

Abstract: Critical COVID-19 disease is accompanied by depletion of plasma tryptophan (TRY) and increases in indoleamine-dioxygenase (IDO)-stimulated production of neuroactive tryptophan catabolites (TRYCATs), including kynurenine (KYN). The TRYCAT pathway has not been studied extensively in association with the physiosomatic and affective symptoms of Long COVID. In the present study, we measured serum TRY, TRYCATs, insulin resistance (using the Homeostatic Model Assessment Index 2-insulin resistance, HOMA2-IR), C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…l -tryptophan catabolism by indoleamine-dioxygenase (IDO) through the kynurenine pathway generates several bioactive metabolites collectively referred to as kynurenines 426 . SARS-CoV-2 infection could deplete plasma l -tryptophan levels and increase IDO-stimulated generation of neuroactive tryptophan catabolites, including kynurenine 427 . Kynurenine is precursor for the vital cellular effector NAD + and for several other intermediate metabolites that modulate immune and neuronal functions.…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…l -tryptophan catabolism by indoleamine-dioxygenase (IDO) through the kynurenine pathway generates several bioactive metabolites collectively referred to as kynurenines 426 . SARS-CoV-2 infection could deplete plasma l -tryptophan levels and increase IDO-stimulated generation of neuroactive tryptophan catabolites, including kynurenine 427 . Kynurenine is precursor for the vital cellular effector NAD + and for several other intermediate metabolites that modulate immune and neuronal functions.…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…4 ), when viral load was reduced 32 , also supports this hypothesis. Very recently, an increased KYN/TRY ratio due to IDO has also been reported in patients with severe COVID 33 . Since IDO and its catabolites kynurenines suppress T-cell responses and promote Treg proliferation 34 , 35 this may be a strategy of the virus to induce immune tolerance.…”
Section: Discussionmentioning
confidence: 90%
“…In COVID-19 patients, other authors observed increased activity of the TRYCAT pathway 60 , 61 , as manifested by decreased tryptophan concentration and increased levels of KN and NFK, resulting from increased IDO activity under the influence of pro-inflammatory cytokines. In addition, the SARS-CoV-2 virus stimulates the aryl hydrocarbon receptor (AhR) and increases KN levels, which leads to the systemic AhR activation syndrome (SAAR) that intensifies inflammation, induces thrombophilia, and contributes to organ damage 62 , 63 .…”
Section: Discussionmentioning
confidence: 95%